nalysis of the Making Questions Ability of Respiratory and Its Function on Elementary School Students in Bandar Lampung City - Pramudiyanti, Pramudiyanti; Rakhmawati, Ismi; Syafitri, Ananda Riska (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
One of the scientific approach activities is asking questions but not every student is actively asking questionswhich can trigger curiosity about learning. This study aims to measure the making questions ability of fifth-grade elementary school students in the city of Bandar Lampung on the subject matter of respiratory organsand functions in animals and humans. This descriptive survey research used a multistage cluster samplingarea combined with the stratification. The design of this research is cross-sectional. The type of data in thisstudy is quantitative data obtained by measuring the ability of students in making questions and the resultswill be interpreted in the form of a percentage which is then categorized based on the category of students'ability in making questions. The making questions ability of students in this study can be measured accordingto the indicators of assessing the quality of the questions. The results of the calculation of the data that havebeen obtained show that the ability of grade V elementary school students in making questions is in highcategory with a final percentage of 70.97%. The results of quality of student questions based on 4 indicatorsobtained the percentage from the highest to the lowest, which is 24.6% on the focus indicator, 17.1% onthe grammar indicator, 15.6% on the relevance indicator, and 13.6% on the cognitive level indicator. Thecognitive level is influenced by age and level of education, grammar is influenced by the limited vocabularyfactor that is owned. It can be concluded that the difficult to arrange questions with good and correctvocabulary relevance with influenced of students' inability to think more critically and deeply so it is difficultfor them to make questions that are relevant to everyday life or other fields of science and the focus isinfluenced by interesting learning media and interactive learning methods